The Integrated Model of Growth in Islamic Educational Psychology: A Deductive Analysis of the Relationship Between the Three Stages of Education and the Macro-Cycle of Human Life - Parnian, Fatemeh; Davoodi, Abdolvahid; Zargam, Majid (Assessment and Practice in Educational Sciences, 2026)
This fundamental research was conducted with the aim of explaining and deriving a coherent developmental psychology model from the perspective of Islam, with a specific focus on educational psychology. In the contemporary era—where Western educational systems face numerous challenges such as identity crises, loss of meaning, and the weakening of the family institution—the reinterpretation and systematization of educational models based on authentic Islamic texts emerge as both a scientific and cultural necessity. The research method employed was a library-based approach combined with deductive and ijtihādī analysis of original Islamic religious sources (the Qur’an, the Prophetic Sunnah, and the traditions of the Ahl al-Bayt), examined in interaction with contemporary findings in developmental psychology. The results indicate that Islam, by presenting two classifications that appear distinct but are in fact deeply complementary—one detailed, practical, and educational (the three developmental stages of ages 0–7, 7–14, and 14–21), and the other holistic, philosophical, and ontological (the stages of first weakness, strength, and second weakness)—offers a comprehensive and multidimensional representation of the human growth and development process. This article argues, through an ijtihādī approach, that the unique and golden developmental period from birth to age 21, formed under purposeful parental nurturing, functions not only as the foundation of an individual’s personality but also as the primary determinant of the quality of one’s transition into the stage of strength (youth and middle adulthood), and even of the lived experience of the stage of second weakness (old age). Within this model, rational education is presented and explained as the core and backbone of the harmonious and integrated development of a child’s other existential dimensions—emotional, social, moral, and physical. Ultimately, the study proposes an “Integrated Islamic Growth Model,” which can serve as a foundation for theorization and practice in the domain of Islamic education.